Process management in Russian business education - Lyudmila V. Dukanich; Svetlana V. Korobeynikova (Высшее образование в России)
This paper presents the outcomes of implementation of the process-orientated approach to business education based on the experience of one of the leading Russian business schools. Formed at the beginning of 1990’s, the current management system in Russian business education has been predominantly based on the principles of functional management, which in turn does not comprehensively address the emerging objectives and terms of modern-day education providers in Russia. The countries’ business schools are of the particular concern of the issue, considering the factors of their recent establishment and revenue-based financing. The implementation of modern-day process-orientated approach in the management system of education providers results in an array of apparent advantages.